Determinan Valuasi Obligasi Negara Ritel Syariah Di Indonesia: Perspektif Makroekonomi Dan Risiko Investasi - Lailul Ilham; Bayu Wijayantini; Achmad Hasan Hafidzi; Karnadi (Institut Agama Islam Yasni Bungo Jambi, Indonesia, 2026)
This study focuses on analyzing the determinants of Indonesian Retail Government Bond (ORI) valuation from the perspectives of macroeconomic conditions and investment risk during the 2014–2024 period. The study examines the effects of inflation, the USD/IDR exchange rate, coupon rates, and sovereign ratings on ORI prices in the secondary market. A quantitative approach with a causal research design was employed, using temporal data collected from Bank Indonesia, the Central Statistics Agency (BPS), and the Directorate General of Financing and Risk Management (DJPPR), the Indonesia Stock Exchange, and international rating agencies. Data processing was carried out using multiple linear regression analysis and Spearman’s rank correlation test, supported by statistical software SPSS.. The findings show that coupon rates significantly affect ORI prices, indicating that investors place greater emphasis on fixed-return characteristics in retail bond valuation. In contrast, inflation, the USD/IDR exchange rate, and sovereign ratings do not show significant effects on ORI prices during the observation period. Simultaneously, the independent variables explain 91.3% of the variation in ORI prices, suggesting a strong explanatory capacity of the proposed model. This study highlights that internal bond characteristics are more dominant in influencing ORI valuation than external macroeconomic factors. The findings contribute to the applied finance literature by providing empirical evidence on retail bond valuation dynamics in emerging markets, particularly within the context of Indonesia’s sovereign retail bond market.